Antimicrobial Activity of Dadap Serep (Erythrina subumbrans (Hassk.) Merr.) Leaves Extract - Utami, Diah Tri (Talenta Publisher, 2019)
The leaves of Erythrina has been used in Indonesia as a remedy for rheumatism, stomach-ache, asthma, dysentery, contact dermatitis, eczema and skin infections. However, there have been limited phytochemical or biological studies on the leaves of E. subumbrans and there are not studies that align with its traditional medicinal uses. The aim of this study was to assess the antimicrobial activity of the leaves of E. subumbrans to support its topical use in the treatment of skin infections. Disc diffusion agar assays were used to determine the antimicrobial activities of ethanol extracts of the leaves of E. subumbrans.The ethanol extracts showed the most significant activity with MIC values of 0,5 Âµg/mL. against a sensitive strain of Staphylococcus epidermidis. Extract concentration of 0,5 mg/ml, 1 mg/ml, 5 mg/ml and 10 mg/ml showed inhibition zone continuously as high as 1,83 mm; 3,42 mm; 5,17 mm, and 8,00 mm. The ethanol extracts of the leaves of E. subumbrans also showed significant activity against Candida albicans with MIC values of 0,5 Âµg/mL. Extract concentration of 0,5 mg/ml, 1 mg/ml, 5 mg/ml and 10 mg/ml showed inhibition zone continuously as high as 4,00 mm; 4,17 mm; 5,25 mm, and 6,50 mm. Bioactive substance test showed that alkaloid, flavonoid, saponin, and triterpenoid were found in E. subumbrans extract indicates potential activity as antimicrobial agent. These results provide support for the customary (traditional and contemporary) use of E.subumbrans leaves for the treatment of nosocomial infections.